My shoelaces are hard to tie! - Roberson, Karla; Holley, Vanessa (New York : Scholastic, 2004)
A young girl gets help from her big brother while learning to tie her shoelaces.
K-Grade 1.
Keywords: Shoelaces -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Perseverance (Ethics) -- Juvenile fiction; Stories in rhyme -- Juvenile fiction